2014
DOI: 10.1682/jrrd.2014.03.0081
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between solid-ankle cushioned heel and energy storage and return prosthetic foot based on step-to-step transition cost

Abstract: Abstract-Decreased push-off power by the prosthetic foot and inadequate roll-over shape of the foot have been shown to increase the energy dissipated during the step-to-step transition in human walking. The aim of this study was to determine whether energy storage and return (ESAR) feet are able to reduce the mechanical energy dissipated during the step-tostep transition. Fifteen males with a unilateral lower-limb amputation walked with their prescribed ESAR foot (VariFlex, Ossur; Reykjavík, Iceland) and with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 36 publications
6
46
0
Order By: Relevance
“…Previous studies suggest that user satisfaction with forward walking on level ground may be a consequence of improvements in prosthetic foot design, with newer designs preferred over older solid-ankle cushioned-heel designs. 21,22 However, participants in our study also identified a number of situations in which their current prosthetic feet caused significant difficulties, often with safety implications. Consequently, forward walking may not be the most sensitive test for prosthetic mobility.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Previous studies suggest that user satisfaction with forward walking on level ground may be a consequence of improvements in prosthetic foot design, with newer designs preferred over older solid-ankle cushioned-heel designs. 21,22 However, participants in our study also identified a number of situations in which their current prosthetic feet caused significant difficulties, often with safety implications. Consequently, forward walking may not be the most sensitive test for prosthetic mobility.…”
Section: Discussionmentioning
confidence: 85%
“…Although both the prosthetic users and professionals in this study attributed the participation restrictions to the prosthetic foot, this causal relationship was not systematically evaluated in our study and other factors (e.g., skin integrity, as described in Meulenbelt et al 21 ). Future studies should provide elucidation of the mechanisms or participation restriction to enable stakeholders to overcome barriers to participation.…”
Section: Discussionmentioning
confidence: 96%
“…Amputees wore their own prostheses with energy storage and return feet, passive elastic feet that provide more propulsion than a solid-ankle cushioned heel foot but less than a powered ankle (Wezenberg et al 2014; Herr, Grabowski, 2012). All amputees had their prostheses for over 6 months before testing.…”
Section: Methodsmentioning
confidence: 99%
“…The increased understanding of the mechanisms underlying gait impairments, as described in part A, can assist in the development and evaluation of prosthetic components. Wezenberg et al [4] compared a rigid prosthetic foot to a prosthetic foot that is able to store and return energy. These latter category is able to provide prosthetic ankle and foot push-off to a limited extent.…”
Section: B Influence Of Prosthetic Componentsmentioning
confidence: 99%